Kepemimpinan Perempuan dalam Lembaga Pendidikan Islam - Lestari, Ayu; Nomi, Ahmad Suryadi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Women's leadership in Islamic educational institutions is the primary focus of this research. This study aims to delve into the contributions, challenges, and policy implications of women's leadership in the context of Islamic education. Employing a qualitative approach and literature review method, this research analyzes various theories and related studies to compile a comprehensive overview of this issue. The findings indicate that women's leadership significantly contributes to the development of Islamic education, both academically and morally. However, challenges such as gender stereotypes, lack of institutional support, and societal perceptions remain obstacles that need to be overcome. A deep discussion on the factors influencing the success or failure of women in leadership positions provides insights into strategies that can be implemented to strengthen women's roles in Islamic educational institutions. Recommendations for educational institutions, governments, and society include enhancing inclusive leadership development programs, implementing gender equality policies, and educating the public about the importance of gender inclusion in education. The implications of this research for Islamic education policies and practices highlight the need for transformation to create a more representative and inclusive learning environment. Thus, this research has the potential to provide guidance for policymakers to enhance women's participation in Islamic educational leadership more broadly.